2017
DOI: 10.3354/meps12321
|View full text |Cite
|
Sign up to set email alerts
|

The invasive kelp Undaria pinnatifida hosts an epifaunal assemblage similar to native seaweeds with comparable morphologies

Abstract: Supplement 1 (A) PERMANOVA results from the analysis of differences between months and species at Aramoana in February/March 2012 and December 2012 (Table S1), pair-wise test among seaweed species (Table S2), and MDS plots of ordination of epifaunal composition by time (Fig. S1) and seaweed species (Fig. S2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Common seaweed-associated reef fishes such as clinids and odacids inhabit wakame patches throughout vitellogenesis and into the spawning period (late winter to late spring: Gunn andThresher 1991, Neira andSporcic 2002, this study). Current evidence indicates that wakame supports a similar abundance and diversity of epifauna to native kelps with comparable morphologies (Howland 2012, Su arez-Jim enez et al 2017. Our data also indicate that adults residing in wakame habitat experience comparable food availability to those in native E. radiata habitats, although this may also reflect lower population density and therefore reduced competition in wakame patches (i.e., an ideal free distribution; Notes: N is presented as "wakame, E.…”
Section: Discussionmentioning
confidence: 57%
“…Common seaweed-associated reef fishes such as clinids and odacids inhabit wakame patches throughout vitellogenesis and into the spawning period (late winter to late spring: Gunn andThresher 1991, Neira andSporcic 2002, this study). Current evidence indicates that wakame supports a similar abundance and diversity of epifauna to native kelps with comparable morphologies (Howland 2012, Su arez-Jim enez et al 2017. Our data also indicate that adults residing in wakame habitat experience comparable food availability to those in native E. radiata habitats, although this may also reflect lower population density and therefore reduced competition in wakame patches (i.e., an ideal free distribution; Notes: N is presented as "wakame, E.…”
Section: Discussionmentioning
confidence: 57%
“…Current evidence indicates that wakame supports a similar abundance and diversity of epifauna to native kelps with comparable morphologies (Howland , Suárez‐Jiménez et al. ). Our data also indicate that adults residing in wakame habitat experience comparable food availability to those in native E. radiata habitats, although this may also reflect lower population density and therefore reduced competition in wakame patches (i.e., an ideal free distribution; Fretwell and Lukas ).…”
Section: Discussionmentioning
confidence: 84%
“…This bias often takes the form of covert hints in the interpretations and discussions of experimental or observational data that show no relationship between origin and impact. In analyzing the density, diversity and composition of epifauna across eight brown seaweed species, including the invasive Undaria pinnatifida , Suárez‐Jiménez et al () concluded that epifaunal traits were unassociated with the origin of the macroalgae, but with the complexity of host morphology, whereby U. pinnatifida (and several indigenous species) have simple morphologies and therefore support depauperate epifaunal assemblages. Yet, despite the fact that the area under study (New Zealand) was colonized by this NIS over 30 years earlier, in their concluding remarks the authors note that "abundances of epifauna at the ecosystem level will be reduced if U. pinnatifida displaces more structurally complex native seaweed species," omitting the obvious fact that that prospective future dominance by any of the indigenous species with a simple morphology will probably lead to the same result.…”
Section: Dissent Debate and Denialismmentioning
confidence: 99%